Prevalence and associated factors of contraceptives acceptance among reproductive age women attending family health clinic - Norsa'adah Bachok; Tengku Norbanee Tengku Hamzah; Zainoremi Che Zakaria; Aidawani Abdullah; Naing, Nyi Nyi (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Contraceptives have effects on the population's fertility and mortality as well as sexually transmitted diseases. The aims of this study were to determine the prevalence and its associated factors of contraceptives acceptance among women attending family health clinic, HUSM. Married women in reproductive age 15 to 49 years old were selected by systematic random sampling. Standardized questionnaires were used to interview 411 women. The prevalence of ever-used contraceptive was 41.8% (95% CI: 37.1, 46.6). The percentages of acceptance were 17.5% (pills), 8.8% (injectables), 8.5% (condom), 6.1 % (IUD) and 6.1 % (traditional methods). The main reasons of using contraceptives were for birth spacing (77.9%) and prevent unintended pregnancy (61.6%). There were no significant differences between contraceptive users and non-users in the mean age of subjects, age at first marriage, menarche, number of birth, abortion and occupation and husbands' age, education and occupation. However there were significant differences between groups in the family income (p = 0.009), subjects' education (p = 0.001) and occupation (p < 0.001). The prevalence of contraceptive acceptance in this study was lower compared to other studies. Hormonal method was the most popular method. Employed or students, higher income and higher educated women were identified as the significant contraceptive acceptors. Health education is needed especially for housewives, lower income and lower educated women.